2021
DOI: 10.3390/su13010388
|View full text |Cite
|
Sign up to set email alerts
|

Response of Morphological Characters and Photosynthetic Characteristics of Haloxylon ammodendron to Water and Salt Stress

Abstract: In arid desert areas, Haloxylon ammodendron plays an important role in maintaining the ecological balance of desert oases. However, there are few studies on the physiological characteristics of Haloxylon ammodendron under an environmental gradient. Here, we studied the changes in the morphological and photosynthetic characteristics and their correlations in Haloxylon ammodendron in the four habitats of the Ebinur Lake wetland. Our results show that in high-water and high-salt habitats, photosynthesis is affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…Future studies are encouraged to investigate the role of GSH and its biosynthesis in nano-enabled plant salt tolerance. (2) Proline is known as one of the most important and effective organic osmotic regulatory substances, which plays an vital role in maintaining osmotic balance and cell membrane integrity ( Siddiqui et al, 2015 ; Hu et al, 2021 ). Besides being effective osmotic regulatory substance, proline is also known as antioxidants to scavenge ROS ( Siddiqui et al, 2015 ; Brahimova et al, 2021 ; Hu et al, 2021 ).…”
Section: Plant’s Ability To Alleviate Oxidative Stress Is Important F...mentioning
confidence: 99%
See 2 more Smart Citations
“…Future studies are encouraged to investigate the role of GSH and its biosynthesis in nano-enabled plant salt tolerance. (2) Proline is known as one of the most important and effective organic osmotic regulatory substances, which plays an vital role in maintaining osmotic balance and cell membrane integrity ( Siddiqui et al, 2015 ; Hu et al, 2021 ). Besides being effective osmotic regulatory substance, proline is also known as antioxidants to scavenge ROS ( Siddiqui et al, 2015 ; Brahimova et al, 2021 ; Hu et al, 2021 ).…”
Section: Plant’s Ability To Alleviate Oxidative Stress Is Important F...mentioning
confidence: 99%
“…(2) Proline is known as one of the most important and effective organic osmotic regulatory substances, which plays an vital role in maintaining osmotic balance and cell membrane integrity ( Siddiqui et al, 2015 ; Hu et al, 2021 ). Besides being effective osmotic regulatory substance, proline is also known as antioxidants to scavenge ROS ( Siddiqui et al, 2015 ; Brahimova et al, 2021 ; Hu et al, 2021 ). Proline is often used as an important physiological indexes in plant salt tolerance ( Siddiqui et al, 2015 ; Hu et al, 2021 ).…”
Section: Plant’s Ability To Alleviate Oxidative Stress Is Important F...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that due to the perennial, deep-root-forming, and strong water-consuming nature of Haloxylon ammodendron , the continuous growth of Haloxylon ammodendron plantations strongly depletes soil moisture, leading to increased soil desiccation, deterioration of soil moisture ecology, and gradual degradation of artificial vegetation in the region. In particular, the planting of large-scale Haloxylon ammodendron plantation forests has exacerbated the decline of soil moisture in the desert region of northwest China [ 23 , 24 , 25 ]. Therefore, the specific objectives of this study are as follows: (1) to study large-scale Haloxylon ammodendron plantations with regard to the soil moisture depletion and desiccation process, along with the formation and development of the DSL, and (2) to determine the changes in the soil moisture content with forest age after Haloxylon ammodendron plantations.…”
Section: Introductionmentioning
confidence: 99%
“…With this change, the water supply in H . ammodendron during the dormancy period is insufficient, which leads to fruit wrinkling or even reduces seed quality during the germination period (Hu et al, 2021 ; Lü et al, 2019 ). The N:P ratio of H .…”
Section: Introductionmentioning
confidence: 99%